PENGEMBANGAN MEDIA PEMBELAJARAN TABUNG SELUNCUR KELERENG UNTUK MENINGKATKAN KEMAMPUAN MENGENAL ANGKA PADA ANAK TUNARUNGU KELAS II DI SLB HOME BASE - Firdayanti Firdayanti; Dwiyatmi Sulasminah; Mustafa Mustafa (-, 2024)
This research examines the development of marble slide tube media in improving the ability to recognize numbers in class II deaf students at SLB Home Base. The formulation of the research problem is: (1) What are the results of the analysis of the needs for the development of a mathematical marble slide tube media in improving the ability to recognize numbers in class II deaf children? (2) What is media design that can improve the ability to recognize numbers in class II deaf children? (3) How is the validity and practicality of the marble slide tube media in improving the ability to recognize numbers in class II deaf children? (4) What is the feasibility of the marble slide tube media in improving the ability to recognize numbers in class II deaf children? The purpose of this study was to find out: (1) The results of the analysis of the needs for the development of mathematical marble slide tube media in improving the ability to recognize numbers in class II deaf children. (2) Media design that can improve the ability to recognize numbers in class II deaf children. (3) The validity and practicality of the marble slide tube media in improving the ability to recognize numbers in class II deaf children. (4) The feasibility of marble slide tube media in improving the ability to recognize numbers in class II deaf children. Data collection techniques are questionnaires and validity tests. The subjects of this study were two validators, namely lecturers from the Department of Special Education. This research is a development research with a 4-D model, namely: the Define Stage, the Design Stage, the Development Stage, and the Dissemination Stage. Data were analyzed by quantitative descriptive analysis. The results of this study concluded that the results of the validity test for the development of marble slide tube media in improving the ability to recognize numbers in class II deaf students at SLB Home Base.